Finance and Development, March 1985. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1985)
This paper anlayzes the role of the International Financial Corporation (IFC) in promoting economic development in developing countries with the private sector. IFC promotes growth of new companies, indigenous companies, and helps to introduce more capital from private sources into developing countries. Many countries need to develop capital market institutions such as stock exchanges, securities companies, leasing companies, and financial intermediaries of one kind or another. IFC has a special department, partly financed by the World Bank, that has provided expertise in these areas to a number of countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet